15‐2: Effective Color Breakup Suppression by a Low‐Cost Global Dimming Backlight for Field‐Sequential‐Color Displays. Issue 1 (May 2016) - Lin, Fang‐Cheng; Teng, Kai‐Tung; Chang, Chi‐Wen; Lin, Ching‐Huan; Huang, Yi‐Pai; Shieh, Han‐Ping D.
Abstract : This paper considers edge‐directed information of an input image to effectively suppress color breakup for a field‐sequential‐color (FSC) display. The edge‐directed concept can be applied on any current color breakup solution or even applying on a global dimming backlight system. From the simulated and emulated results, the edge‐directed FSC method significantly suppresses color breakup as using Stencil‐FSC with 12×24 backlight segments. Hence, the proposed edge‐directed FSC method can much reduce the computational complexity and make an FSC display more promising as next generation eco‐displays.